2020
DOI: 10.1111/obr.13127
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy overweight/obesity are associated with increased risk of cardiovascular disease in adults, even in the absence of metabolic risk factors: A systematic review and meta‐analysis of prospective cohort studies

Abstract: This review examined the risk of cardiovascular disease in adults with metabolically healthy overweight/obesity. A systematic review and meta-analysis using data from Medline, EMBASE, SCOPUS and Cochrane Library searched from inception up to 31st October 2019. We included prospective cohort studies of adults who are metabolically healthy or unhealthy. Outcomes were fatal and nonfatal cardiovascular events, all-cause mortality. Pooled relative risk was calculated for each outcome in populations with metabolical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 46 publications
1
62
3
Order By: Relevance
“…Finally, one should mention that our results were somewhat different in men and women: there was a higher risk of clinical events in men with MHO compared with metabolically healthy men of normal weight, but a lower risk for most events in women with MHO than in metabolically healthy women of normal weight. The recent meta-analysis conducted by Opio et al 8 30 which may partly explain our different results in men and women.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Finally, one should mention that our results were somewhat different in men and women: there was a higher risk of clinical events in men with MHO compared with metabolically healthy men of normal weight, but a lower risk for most events in women with MHO than in metabolically healthy women of normal weight. The recent meta-analysis conducted by Opio et al 8 30 which may partly explain our different results in men and women.…”
Section: Discussionmentioning
confidence: 75%
“…Several meta-analyses have reported that, compared with metabolically healthy individuals of normal weight, those with MHO are at an increased risk of CV events. 8,16 Another meta-analysis, which examined the association between MHO and CV events and was limited to studies using the strictest definition for metabolic health (i.e. an absence of all metabolic abnormalities), reported an insignificant association between MHO and CV events.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we show that the relationships between BMI and CVD mortality in a Norwegian population differ by sex: with no or negative association in women and positive association in men. A meta-analysis of 21 prospective studies showed that compared to the MHNO group, the HR for CVD in women with MHO were lower than those in men with MHO (HR 1.71 vs 2.15, respectively) (34). However, the meta-analysis included few sex-strati ed studies.…”
Section: Discussionmentioning
confidence: 99%
“…Modifiable risk factors such as unhealthy lifestyle behaviour contribute to the shifting disease burden and so should primarily targeted [3], particularly for cardiovascular diseases' prevention [4,5]. Systematic reviews and meta-analyses have assessed the relationships between the modifiable lifestyle factors such as the alcohol consumption [6], tobacco use [7,8], oral hygiene practices [9], fruit and/or vegetable (FV) consumption [10,11], physical inactivity [12] excess weight [13][14][15] and the metabolic disorders. The World Health Organization (WHO) recommends the implementation of a national surveillance system for the risk factors for the NCDs (stepwise approach to surveillance [STEPS]) including those for cardiovascular diseases [16] and while the US Centre for Disease Control and Prevention recommends the Behavioural Risk Factor Surveillance System [17].…”
Section: Introductionmentioning
confidence: 99%